Impact of COVID-19 control measures on respiratory syncytial virus and hand-foot-and-mouth disease transmission in Hong Kong and South Korea - Yiu Chung Lau; Sukhyun Ryu; Zhanwei Du; Lin Wang; Peng Wu; Eric H.Y. Lau; Benjamin J. Cowling; Sheikh Taslim Ali (Epidemics)
The public health and social measures (PHSMs) for mitigation/control of COVID-19 pandemic influenced the transmission dynamics of many other infectious diseases, including respiratory syncytial virus (RSV) infection, and hand, foot and mouth disease (HFMD) and their disease-burden. This study aimed to infer the transmission dynamics of these respiratory viruses and assess the impact of COVID-19 PHSMs on their community activity. We developed a compartmental framework to infer the transmission dynamics of RSV and HFMD in Hong Kong and South Korea from January 2014 to May 2024. We assessed the impact of PHSMs by comparing the change in virus transmissibility, reproduction number and population susceptibility before, during, and after the COVID-19 pandemic period. A significant reduction in RSV and HFMD activity was observed starting in January 2020, with a resurgence since late 2021. Transmissibility of both diseases decreased by 46 % - 95 % during the lull, while population susceptibility was estimated to increase by maximum of 19 %. On relaxation of the PHSMs, the transmissibility were recovered up to 70 % in Hong Kong and nearly 100 % in South Korea in 2023 with significant epidemics for these viruses. Strict implementation of COVID-19 PHSMs led to low RSV and HFMD activity, but the absence of community infection resulted in reductions in population immunity, and slightly larger epidemics when these diseases re-emerged following the COVID-19 pandemic.